2019
DOI: 10.1111/tpj.14603
|View full text |Cite
|
Sign up to set email alerts
|

Combining GAL4 GFP enhancer trap with split luciferase to measure spatiotemporal promoter activity in Arabidopsis

Abstract: In multicellular organisms different types of tissues have distinct gene expression profiles associated with specific function or structure of the cell. Quantification of gene expression in whole organs or whole organisms can give misleading information about levels or dynamics of expression in specific cell types. Tissueor cell-specific analysis of gene expression has potential to enhance our understanding of gene regulation and interactions of cell signalling networks. The Arabidopsis circadian oscillator is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 66 publications
(108 reference statements)
0
5
0
Order By: Relevance
“…One construct, expressed under a circadian promoter, comprises the C-terminal half of luciferase fused to the C-terminus of A-Fos. A second construct consisting of the N-terminal half of luciferase fused to the bZIP domain of c-Jun is constitutively expressed under a tissue-specific promoter (either directly or indirectly through a UAS promoter transactivated by enhancer trap-driven expression of GAL4; Román et al, 2020 ). When both constructs are expressed together, the A-Fos and c-Jun domains facilitate dimerization, bringing the two halves of luciferase into close proximity to reconstitute enzymatic activity ( Endo et al, 2014 ), generating luminescence from circadian rhythms only in a target tissue (e.g.…”
Section: Section 3: Technical Advances For Analyzing Spatial Specific...mentioning
confidence: 99%
See 2 more Smart Citations
“…One construct, expressed under a circadian promoter, comprises the C-terminal half of luciferase fused to the C-terminus of A-Fos. A second construct consisting of the N-terminal half of luciferase fused to the bZIP domain of c-Jun is constitutively expressed under a tissue-specific promoter (either directly or indirectly through a UAS promoter transactivated by enhancer trap-driven expression of GAL4; Román et al, 2020 ). When both constructs are expressed together, the A-Fos and c-Jun domains facilitate dimerization, bringing the two halves of luciferase into close proximity to reconstitute enzymatic activity ( Endo et al, 2014 ), generating luminescence from circadian rhythms only in a target tissue (e.g.…”
Section: Section 3: Technical Advances For Analyzing Spatial Specific...mentioning
confidence: 99%
“…Enhancer trap split-luciferase assays further refine this method by expressing the c-Jun-nano luciferase (nLUC) fusion under a UAS promoter, which is activated by binding of GAL4. Expressing GAL4 using enhancer trap systems, which consists of previously characterized lines that drive strong tissue-specific expression under a single enhancer ( Shima et al, 2016 ), avoids the need to use full promoters, which can introduce unwanted regulatory effects ( Román et al, 2020 ). However, spatial position of cells can affect clock gene expression even within the same tissue ( Fukuda et al, 2007 ; Wenden et al, 2012 ; Gould et al, 2018 ).…”
Section: Section 3: Technical Advances For Analyzing Spatial Specific...mentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that calli induced from hypocotyls, leaves, and roots showed a similar expression pattern compared to callus from whole seedlings, suggesting that initial tissues did not affect the circadian rhythms in the callus (Figure 4). Several studies indicated that the circadian clock function is tissue-and cell-specific (Thain et al 2002;Takahashi et al 2015;Endo et al 2014;Román et al 2020;Gould et al 2018;James et al 2008;Greenwood et al 2019). At the tissue level, the root clock is less robust and precise than the shoot clock (Thain et al 2002;Takahashi et al 2015;Chen et al 2020) Importantly, the seedling-like rhythms obtained in callus, independent of callus source or media, indicate that freshly-derived callus can be a useful tool for studying circadian regulation.…”
Section: Callus Induction Media and Types Of Explant Did Not Alter Ci...mentioning
confidence: 99%
“…Enhancer trap lines can mark phenotypes that could not otherwise be easily accessible through conventional, loss‐of‐function genetic screens, for example, due to lethal effects of disrupting gene activity, or cryptic mutant phenotypes (Rojas‐Pierce & Springer, 2003 ). In such situations, locating the site of insertion within the genome can identify new gene functions and important novel promoter elements, that can then be used in further research (Radoeva et al., 2016 ; Román et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%